Plan de capacitacion para el talento humano de la Cooperativa de Ahorro y Crédito Policía Nacional Ltda, sucursal Quevedo provincia de Los Rios - Mendoza Tuárez, Luis Augusto (2012)
The completion of this research leads to improved quality of service provided by employees of the Cooperative Credit Union Ltd National Police, branch Quevedo, right through the development of a training plan. While performing this research was audibly obvious standing grievances of the members who feel dissatisfied with the type of service provided by employees of this important financial institution, the starting point for conducting this research paper. The research problem was based on the lack of a training plan in the institution, leading to propose a hypothesis according to research reality, it was necessary to provide input from a group of literary expert authors human resource management to enhance knowledge. For the development of this research was necessary to use various techniques and field research, descriptive literature and inductive methods, synthetic, to contribute to the realization of this work, a methodology was developed that made it as follows proceeded to develop surveys to employees and partners, and interviews the CEO, we proceeded to graph, analyze each answer given by the surveyed population, which reflects the complaint of the members who feel dissatisfied with the attention given, reflecting the main cause non-employee training. Once he met the primary need of the employees noticed the priority and importance to be implementing a training plan that allowed it to develop it as follows: 1. Established general and specific objectives of the proposal, and knew the importance and feasibility is proposed. 2. Developed the proposal, which was to develop a training plan, it is structured as follows: - Developed a training needs assessment. - A plan of work. the same as that identified the areas to be trained. - Prepared the budget of the training. - It set a schedule of activities. 3. He knew the impact of implementing the proposal in the institution. Finally it was necessary to establish mechanisms for ongoing evaluation of training plan, it is explained as follows: Meeting with management, SWOT analysis of the days of training, employees diagnostics, analysis of the topics covered in the training and hold general meetings with human talent working in the institution. In this way the proposal was developed in this research work, waiting for it to have the acceptance and application within the institution, and finally arrived at conclusions and recommendations of the research project.